Energy Financing in Colombia: A Bibliometric Review - Niebles-Nunez, William; Niebles-Nunez, Leonardo; Babilonia, Lorena Hoyos (International Journal of Energy Economics and Policy, 2022)
This article presents a bibliometric review on the researching topic "Contribution to the competitiveness of energy financing in the Colombian business sector", limited from 2011 to 2021. The review was carried out using the Scopus database, obtaining a set of 76 studies in Colombia within the 2609 documents analyzed. After having applied the different filters and search strategies, these studies were analyzed using the Bibliometrix package of the statistical software R. The results identified, for example, that the world production of publications shows an upward trend, with the largest number of scientific investigations presented in 2020. It was also found that one of the most relevant sources is the International Journal of Energy Economics and politics, with five published documents. On the other hand, the most cited local source is Energy Policy magazine, with 90 citations and that the most cited local authors are Cadavid L.